Evaluation of Fatty Acid Profile in Red Tilapia Fed Black Soldier Fly Larvae and Tofu Waste-Based Diets - Purwanto, Ukhradiya Magharaniq Safira; Sari, Sintia Permata; Nabilla, Rahmah; Andrianto, Dimas; Safithri, Mega (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract    Highlight Research Feed formulations based on black soldier fly (BSF) larvae and tofu waste meet the quality requirements based on the Indonesian National Standard Feed formulations based on black soldier fly (BSF) larvae and tofu waste improve fish growth performance comparable to commercial feed Feed formulations based on black soldier fly (BSF) larvae and tofu waste did not increase the level of cholesterol content in fish flesh Fish flesh with black soldier fly (BSF) larvae and tofu waste diet have higher total fatty acid content compared to commercial feed     Abstract Despite growing interest in sustainable aquaculture, studies on the combined use of Black Soldier Fly Larvae (BSFL) and tofu waste as alternative protein sources in tilapia diets, particularly their effects on fatty acid profiles, remain limited. This study evaluates the effects of fish feed formulated with BSFL and tofu waste on the growth performance, proximate composition, and fatty acid profile of red tilapia (Oreochromis niloticus). Experimental diets included: commercial feed, dried BSFL, and a combination of BSFL:tofu waste. Fish were reared for eight weeks under controlled conditions. Treatment with BSFL:tofu waste exhibited superior growth performance, with the highest weight gain (102.88%) and length gain (33.75%). Proximate analysis revealed significant variations across treatments, with a combination of BSFL:tofu waste achieving the highest caloric value (110.71 cal/g) and fat content (3.75%) while maintaining protein levels comparable to commercial feed. Fatty acid analysis showed a combination of BSFL:tofu waste enhanced total fatty acid content (77.92%), predominantly polyunsaturated fatty acids (PUFAs), increasing from 37.34% in commercial feed to 47.04%. Essential fatty acids, including DHA and linoleic acid, were elevated in a combination of BSFL:tofu waste, indicating improved nutritional quality. Cholesterol levels remained unaffected among treatments. These findings suggest that combining BSFL and tofu waste can enhance fish feed quality, optimize growth performance, and improve the nutritional value of red tilapia. Future research should explore refining feed formulations to maximize nutrient stability and sustainability for broader aquaculture applications.